Studies on human papillomavirus (HPV) 16 E2, E5 and E7 mRNA in HPV-positive tonsillar and base of tongue cancer in relation to clinical outcome and immunological parameters. Issue 12 (December 2015) - Ramqvist, Torbjörn; Mints, Michael; Tertipis, Nikolaos; Näsman, Anders; Romanitan, Mircea; Dalianis, Tina
Highlights: Most HPV 16 DNA positive TSCC and BOTSCC biopsies expressed HPV16 E7 mRNA. Of HPV16 DNA E7 mRNA positive TSCC and BOTSCC, 65% also expressed E2 and E5 mRNA. HPV16 DNA positive/E2 mRNA negative TSCC and BOTSCC had worse prognosis. HPV16 E2, E5 and E7 mRNA expression was not correlated to HLA class I expression. HPV16 E2, E5 and E7 mRNA expression was not correlated to CD8 + TIL counts. Summary: Objectives: Three-year survival is 80% for human papillomavirus (HPV) positive tonsillar and base of tongue squamous cell carcinoma (TSCC and BOTSCC) and higher (95–100%) in patients with tumors without HLA class I expression, or with high CD8 + tumor-infiltrating lymphocyte (TIL) counts. The former paradoxical, the latter expected, but it is known that E5 and E7 can downregulate HLA class I expression. Furthermore, upon HPV integration, E2, sometimes in combination with E5 is lost. Here, HPV16 E2, E5 and E7 mRNA was therefore examined in relation to HLA class I expression, TIL counts and survival. Patients and methods: HPV16 DNA positive TSCC and BOTSCC biopsies, analyzed for HLA class I and CD8 + TILs, of 133 patients, treated curatively between 2000 and 2011, were tested for HPV16 E2, E5 and E7 mRNA expression. Totally 127 samples could be evaluated and of these 117 patients, all with HPV16/E7-mRNA-positive tumors, were included in the final analysis. Results: Most tumors (92%) expressed E7 mRNA, and of these 64% also expressed E2 and E5 mRNA. Patients with tumors lacking E2 mRNA had worse 3-year relapse and progression free survival ( p  < 0.01 and p  < 0.05), while presence of E5 had no impact on clinical outcome. Furthermore, HLA class I expression and TILs were not correlated to E5 or to E2 mRNA expression. Conclusion: Lack of E2 but not E5 mRNA in HPV16 positive TSCC and BOTSCC was a negative prognostic marker. Presence of HPV16 E2, E5 and E7 mRNA expression was not correlated to HLA class I expression or CD8 + TILs.